Blockchain-Enabled Information Systems for Transparent GHG Reporting in Maritime Training Organizations - Jaja Suparman; Markus Yando; Nafi Almuzani; Ikhwanuddin, Ikhwanuddin; Aditya Rinaldi (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
This study investigates the transformative potential of blockchain-enabled information systems for transparent greenhouse gas (GHG) reporting in maritime training organizations, addressing critical gaps in regulatory compliance and environmental accountability. Through qualitative thematic analysis of in-depth interviews with five maritime education professionals, this research examines how distributed ledger technology can revolutionize compliance with emerging EU regulations, including FuelEU Maritime directives and EU Emissions Trading System (ETS) requirements, alongside International Maritime Organization (IMO) standards. The study reveals that blockchain technology offers unprecedented solutions to longstanding challenges in maritime education systems, particularly in transparency, verification accuracy, and cross-organizational interoperability. Key findings highlight the technology's capacity to enable smart contract automation for real-time compliance monitoring, create immutable credentialing systems that enhance trust among stakeholders, and establish secure, tamper-proof records of seafarer competency development and environmental certification processes. Results demonstrate that blockchain-based systems can significantly strengthen the integrity of maritime training records while streamlining regulatory reporting processes.